2015
DOI: 10.1090/conm/635/12678
|View full text |Cite
|
Sign up to set email alerts
|

Transverse instability of plane wave soliton solutions of the Novikov-Veselov equation

Abstract: Abstract. The Novikov-Veselov (NV) equation is a dispersive (2+1)-dimensional nonlinear evolution equation that generalizes the (1+1)-dimensional Korteweg-deVries (KdV) equation. This paper considers the stability of plane wave soliton solutions of the NV equation to transverse perturbations. To investigate the behavior of the perturbations, a hybrid semi-implicit/spectral numerical scheme was developed, applicable to other nonlinear PDE systems. Numerical simulations of the evolution of transversely perturbed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…An example of this are the solutions generated by Hirota's method, see section 4.2.1. This solution is unstable with respect to perturbations periodic in y direction with period 2 π k √ c for 0.363 < k < 1, see [16]. This is confirmed by numerical evolution of the NV equation using the above spectral method.…”
Section: Special Solutionssupporting
confidence: 62%
See 3 more Smart Citations
“…An example of this are the solutions generated by Hirota's method, see section 4.2.1. This solution is unstable with respect to perturbations periodic in y direction with period 2 π k √ c for 0.363 < k < 1, see [16]. This is confirmed by numerical evolution of the NV equation using the above spectral method.…”
Section: Special Solutionssupporting
confidence: 62%
“…There is a close connection between plane wave solutions to NV and solutions to KdV (see [16]): for some direction vector n = (n 1 , n 2 ) = (cos(α), sin(α)). Then the bounded solutions to the ∂ equation (4.2) are given by…”
Section: Special Solutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many articles were dedicated to unusual and fascinating properties of the multi-dimensional solutions, including those for seemingly ordinary flat waves. In particular, in [24] it has been shown that plane wave soliton solutions of NV equation are not stable for transverse perturbations; the paper [18] demonstrates that NV equation permits such interesting solutions as multi-solitons, ring solitons, and the breathers; while the authors of [25] construct a Mach-type soliton of the NV equation. One of the most effective mathematical tools for studying the NV equation is the inverse scattering method.…”
Section: Introductionmentioning
confidence: 99%